Fractal Dimension Characteristics of the Soil Cracking Process When Saline-Alkali Soil Is Mixed with Hippophae Roots - Lichuang Jin; Shuai Zhang; Yingjie Xu (Fractal and Fractional, 2022)
Fractal analysis is an effective tool to describe real world phenomena. Water evaporation from the soil surface under extreme climatic conditions, such as drought, causes salt to accumulate in the soil, resulting in soil salinization, which aggravates soil shrinkage, deformation, and cracking. Hippophae is an alkali tolerant plant that is widely grown in Northwest China. Laboratory drying shrinkage tests of Saline-Alkali soil samples with 0%, 0.5%, 1%, and 2% concentrations of hippophae roots were carried out to study the effect of hippophae roots on the evaporation and cracking of Saline-Alkali soil and to determine variation characteristics of the soil samples’ fractal dimensions. A series of changes in the cracking parameters of Saline-Alkali soil were obtained during the cracking period. Based on fractal theory and the powerful image processing function of ImageJ software, the relationships between samples’ cracking process parameters were evaluated qualitatively and quantitatively. The experimental results show that the residual water contents of Saline-Alkali soil samples with 0%, 0.5%, 1%, and 2% concentrations of hippophae roots were 2.887%, 4.086%, 5.366%, and 6.696%, respectively. The residual water content of Saline-Alkali soil samples with 0.5% and 1% concentrations of hippophae roots increased by 41.53% and 85.87%, respectively; the residual water content of the sample with a 2% concentration of hippophae roots was 131.94% higher than that of the sample without hippophae roots. The final crack ratios of Saline-Alkali soil samples with 0%, 0.5%, 1%, and 2% concentrations of hippophae roots were 21.34%, 20.3%, 18.93%, and 17.18%, respectively. The final crack ratios of Saline-Alkali soil samples with 0.5%, 1%, and 2% concentrations of hippophae roots reduced by 4.87%, 11.29%, and 19.49%, respectively, compared with that of the sample without hippophae roots. Fractal dimensions at the end of cracking were 1.6217, 1.5656, 1.5282, and 1.4568, respectively. Fractal dimensions increased with an increase in the crack ratio and with a decrease in water content. The relationship between water content and fractal dimension can be expressed using a quadratic function. Results indicate that hippophae roots can effectively inhibit the cracking of Saline-Alkali soil and improve its water holding capacity.